HUBUNGAN LAMANYA HEMODIALISA DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS DI RSU KABUPATEN TANGERANG - Lastri Mei Winarni; Ridwan Ridwan (Universitas Yatsi Madani, 2017)
Hemodialysis duration of the results of research conducted 53 respondents obtained frequency distribution of new hemodialysis as many 15 people (28,3%), duration of medium hemodialysis as many 10 people (18,9%) and duration of long group hemodialysis as many 28 people (52,8%). Quality of life patients with chronic renal failure of the results conducted 53 respondents obtained frequency distribution quite quality of life as many 31 people (58,5%), good quality of life as many 22 people (41,5%) and none of respondents have less quality of life. Purpose of research for to know duration of hemodialysis with the quality of life patients with chronic renal failure. Research Methods used in this research is descriptive correlation with cross sectional. Research sites in RSU Kabupaten Tangerang. The sampling technique is simple random sampling with a total sample 53 respondents. Result showed by chi-square test p-value 0,694 obtained where value > α (0,05), it is Ho accepted, which means there is no relationship between duration of hemodilysis with the quality of life pattients with chronic renal failure in RSU Kabupaten Tangerang 2016. Conclusions from the study there is no relationship duration of hemodilysis with the quality of life pattients with chronic renal failure..